Graphene under direct compression: Stress effects and interlayer coupling. Issue 12 (23rd August 2016) - del Corro, Elena; Peña‐Álvarez, Miriam; Mračko, Michal; Kolman, Radek; Kalbáč, Martin; Kavan, Ladislav; Frank, Otakar
Abstract : In this work we explore mechanical properties of graphene samples of variable thickness. For this purpose, we coupled a high pressure sapphire anvil cell to a microRaman spectrometer. From the evolution of the G band frequency with stress, we document the importance the substrate has on the mechanical response of graphene. On the other hand, the appearance of disorder as a consequence of the stress treatment has a negligible effect on the high stress behavior of graphene. Isotopic labeled twisted bilayer graphene under compression characterized by Raman spectroscopy.